Penerapan Lembar Kerja Siswa Berbasis Etnosains untuk Melatih Keterampilan Penyelesaian Masalah Siswa Kelas VII - Aninten, Aninten (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
This research aims to determine students' problem solving skills after using Ethnoscience-based worksheets. This type of research is pre-experimental. The test subjects for this research were class VII students at MTS Nurul Islam Sekar Bela Mataram for the 2022/2023 academic year. The research design for this research was One Group Pretest Posttest Design. The instruments used in this research were problem solving skills tests, and ethnoscience-based LKS validation sheets. The validation sheet is used to validate the ethnoscience-based worksheet that has been prepared. The data analysis technique used in this research uses N-Gain score data analysis. The sampling technique is not chosen randomly (non-randam sampling). The research results show that problem solving skills in class VIIB show an N-Gain score of 0.14, which is in the low category. In class VIIE, the N-Gain score of 0.10 is in the low category. So the results of this research can be concluded that students' problem solving skills have increased even though they are in the low category. Students' problem solving skills applying the ethnoscience-based learning model can improve students' problem solving skills after using ethnoscience-based worksheets on environmental pollution material in classes VIIE and VIIB.